(untitled) (Salduie, 2025)
In this work we present two countermarks (AVC/AVG and TA) that we find widely attested in multiple finds made from the limes, but that are unknown within the coins minted in Hispania. These countermarks are present in the Gallic workshops, passing through both lower and upper Germania, continuing through Pannonia, Thrace, Moesia and of course on coins minted in the mint of Rome. Their appearance has been recorded on aces, duponds and sesterces, as well as on coins of practically all the emperors of the Julio-Claudian dynasty, these countermarks have undergone countless transformations in their design and production. In the case of the coins presented here, they appear placed on coins from the Colonia Victrix Iulia Celsa mint, one of the most important mints in the Ebro Valley that supplied cash to the legions stationed during the cantabrian wars.